Head to head comparison of two commercial fecal calprotectin kits as predictor of Mayo endoscopic sub-score and mucosal TNF expression in ulcerative colitis - Goll, Rasmus (PLoS One, 2019)
BACKGROUND: Fecal calprotectin is widely used to monitor disease activity in patients with inflammatory bowel disease. Multiple commercial kits exist, however, since the analyses are not standardized, these kits cannot be used interchangeably. We aimed to perform a technical evaluation of two kits (Calpro from Calprolab, Norway and Calprest from Eurospital, Italy) and perform a tuning for detection of clinically relevant disease states in ulcerative colitis. MATERIALS AND METHODS: For tuning against different clinical states a total of 116 patients with ulcerative colitis were recruited (67 of which were part of an earlier publication). For the technical evaluation an additional series of 80 random samples from the hospital lab were included. Technical evaluation was done by correlation and limits of agreement analysis; cut-off levels were explored by ROC analysis against clinically relevant actual states. RESULTS: The technical evaluation revealed good correlation between assays, however a non-linear difference was found: At values below 200 mg/kg, no significant bias was found; in the interval 200–1000 mg/kg the Calprest assay measured on average 30% lower than Calpro; and at higher values Calprest measured 60% higher values than Calpro. Both assays predicted Mayo endoscopic score (MES) 0 (cutoff 28: sensitivity 0.38; specificity 0.82 for Calprest; cutoff 28: sensitivity 0.50; specificity 0.77 for Calpro), and MES 2–3 (cutoff 148: sensitivity 0.72; specificity 0.80 for Calprest; cutoff 208: sensitivity 0.64; specificity 0.80 for Calpro), but did not predict normalization of mucosal TNF transcript per se. A combination of calprotectin and MES predicted mucosal TNF transcript values reasonably well (Calpro: sensitivity 0.85, specificity 0.58; Calprest: sensitivity 0.85, specificity 0.61). CONCLUSION: The Calpro and Calprest assays correlated well, but subtle differences were found, underlining the need for kit-specific cut-off values. Both kits were most precise in predicting active inflammation (MES 2–3), but less so for prediction of mucosal healing (MES 0) and normalization of mucosal TNF gene expression.